Hubungan antara Kemandirian Belajar dengan Hasil Belajar Bahasa Arab: Studi terhadap Santri di Pondok Pesantren Nashrul Haq Al-Islamy Sukarindik, Kota Tasikmalaya - Aulia, Qisti Shoffa; Darusman, Yus; Laksono, Bayu Adi (Ta'limi | Journal of Arabic Education and Arabic Studies, 2023)
In a learning activity, an individual is an actor in determining the success of the learning process. Learning results will be less than maximum when there is no awareness, will, or involvement of students in learning. As a student should be able to take responsibility for what he has done and not rely on others to do the task, every student should have an attitude of learning independence. This study aims to be able to know: 1) the relationship between independence of learning and the results of learning Arabic in Nashrul Haq Al-Islamy; 2) the independence of studying in Pondok Pesantren Nashrul Haq Al-Islamy; and 3) the results of studying Arabic at Nashral Haq El-Iislamy. The quantitative approach used in this study is correlational. The study involved a sample of 49 cells. Data is then collected using an analytical research instrument. Of the 30 statements tested first, only 20 could be validated, with a reliability value of 0.814. The results of the study of students at the Nashrul Haq Al-Islamy Training Hall showed that learning independence was at a high score of 80, while learning results were in the middle category of 79. The relationship and significance between the independence of learning and the results of learning Arabic in Nashrul Haq Al-Islamy are in a very low category. It is that the correlation value is 0.047 and the significance value is 0.747, which means more than 0.05 (0.747>0.05). Based on the results of the study, H1 in this study was rejected. Therefore, there is no significant connection between independent learning and the results of learning Arabic in the Nashrul Haq Al-Islamy Residence